Meeting national targets and global commitments with systems thinking - Mosnier, Aline; DeClerck, Fabrice A.J. (CGIAR System Organization, 2023)
From the Sustainable Development Goals to national nutrition targets, the proliferation of national and global sustainability goals in recent decades reflects the growing urgency of achieving healthy diets while staying within planetary boundaries. As the pledges and commitments multiply, however, how can we be sure that they are not counteracting each other? Is it possible for countries to minimize trade-offs across the water–energy–food–ecosystems nexus and achieve both national and international goals?